Effects of 2,4-d herbicide on species of the digitaria genus - Gazola, T. [UNESP]; Dias, M. F. [UNESP]; Dias, R. C. [UNESP]; Carbonari, C. A. [UNESP]; Velini, E. D. [UNESP] (FapUNIFESP (SciELO), 2019)
The objective of this work was to evaluate the effects of the 2,4-D herbicide on the growth and development of Digitaria insularis and Digitaria horizontalis plants under different climatic conditions. Two greenhouse experiments were conducted in a completely randomized design, with 11 treatments (rates of the herbicide) and four replications. Rate-response curves were determined for the 2,4-D rates of 0, 50.37, 100.75, 201.5, 403, 806, 1,612, 3,224, 6,448, 12,896, and 25,792 g a.i. ha-1. The plants presented growth stimulus with low rates of 2,4-D in the autumn-winter period, but this stimulus was not found in the spring-summer period. The plants subjected to application of high rates of 2,4-D had significantly lower growth and development than the control, regardless of the climatic conditions. Therefore, auxin herbicides must be used with caution, mainly in periods of low temperatures, because any problems related to the application technology – which may cause the contact of plants with low rates of this herbicide – will promote the growth of plants of these species, hindering the control and favoring the dispersion of these plants.
Efeitos do Herbicida 2,4-D em Espécies do Gênero Digitaria
Keywords: Digitaria horizontalis; Digitaria insularis; Hormesis; Synthetic auxin